Effect of Exogenous Siderophores on Iron Uptake Activity of Marine Bacteria under Iron-Limited Conditions - Guan, Le Luo (American Society for Microbiology, 2001)
More than 60% of species examined from a total of 421 strains of heterotrophic marine bacteria which were isolated from marine sponges and seawater were observed to have no detectable siderophore production even when Fe(III) was present in the culture medium at a concentration of 1.0 pM. The growth of one such non-siderophore-producing strain, alpha proteobacterium V0210, was stimulated under iron-limited conditions with the addition of an isolated exogenous siderophore, N,N′-bis (2,3-dihydroxybenzoyl)-O-serylserine from a Vibrio sp. Growth was also stimulated by the addition of three exogenous siderophore extracts from siderophore-producing bacteria. Radioisotope studies using (59)Fe showed that the iron uptake ability of V0210 increased only with the addition of exogenous siderophores. Biosynthesis of a hydroxamate siderophore by V0210 was shown by paper electrophoresis and chemical assays for the detection of hydroxamates and catechols. An 85-kDa iron-regulated outer membrane protein was induced only under iron-limited conditions in the presence of exogenous siderophores. This is the first report of bacterial iron uptake through an induced siderophore in response to exogenous siderophores. Our results suggest that siderophores are necessary signaling compounds for growth and for iron uptake by some non-siderophore-producing marine bacteria under iron-limited conditions.